A Qualitative Assessment of Emergency Department Patients' Knowledge, Beliefs, Attitudes, and Acceptance Toward Revised HIV Testing Strategies. (20th March 2013) - Cowan, Ethan; Leider, Jason; Velastegui, Lorena; Wexler, Juliana; Velloza, Jennifer; Calderon, Yvette; Bogucki, Sandy
Abstract Objectives The objective of this study was to explore emergency department (EDs) patients' knowledge, beliefs, attitudes, and acceptability toward revised human immunodeficiency virus (HIV) testing recommendations. Methods Participants were recruited in proportion to the racial, sex, and ethnic makeup of the study ED. Interviewers presented participants with a stimulus followed by questions about opt‐out consent, elimination of separate written consent, and curtailed counseling. Three investigators coded all transcripts using an iterative coding strategy until thematic saturation was achieved. Results Thirty‐four semistructured, in‐depth, individual interviews were conducted, including five with patients ages 13 to 17 years and five with Spanish‐speaking patients. Nineteen (56%) participants were women. The mean (±SD) age was 31 (±12) years. Most were Hispanic (38%) or African American/black (44%). Only one (2.9%) participant knew about the revised testing recommendations. Participants believed that opt‐out consent would result in increased testing, but this was confounded by misunderstanding of the consent process: "so the opt‐out is, you basically don't have a choice." Participants thought eliminating separate written consent was a positive change but that it could result in people being tested without their knowledge. Attitudes diverged over curtailed counseling, but participants felt patients "should have options" for counseling because "everybody isn't the same." Conclusions Emergency department patients were unaware of revised HIV testing recommendations. Most felt that opt‐out consent and elimination of separate written consent were positive changes but could result in a patient being tested without his or her knowledge. The response to curtailed counseling was polarized but participants agreed on the need to accommodate personal preferences. This information may be useful when designing ED‐based HIV testing programs.